2022
DOI: 10.3390/ijms23095159
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutritional Status, Gastrointestinal Peptides, and Endocannabinoids in the Prognosis and Treatment of Children with Cancer

Abstract: Neoplastic diseases in children are the second most frequent cause of death among the young. It is estimated that 400,000 children worldwide will be diagnosed with cancer each year. The nutritional status at diagnosis is a prognostic indicator and influences the treatment tolerance. Both malnutrition and obesity increase the risk of mortality and complications during treatment. It is necessary to constantly search for new factors that impair the nutritional status. The endocannabinoid system (ECS) is a signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…Schab et. al mentioned studies have shown that cannabinoids have hindered the growth of rhabdomyosarcoma and neuroblastoma cells and stopped cell cycle progression in osteosarcoma cells in children [11]. Moreover, it was found that CB1 expression may help foreshadow the shrinking of lowgrade gliomas in children [11].…”
Section: Use Of Cannabis In Cancer Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Schab et. al mentioned studies have shown that cannabinoids have hindered the growth of rhabdomyosarcoma and neuroblastoma cells and stopped cell cycle progression in osteosarcoma cells in children [11]. Moreover, it was found that CB1 expression may help foreshadow the shrinking of lowgrade gliomas in children [11].…”
Section: Use Of Cannabis In Cancer Treatmentmentioning
confidence: 98%
“…al mentioned studies have shown that cannabinoids have hindered the growth of rhabdomyosarcoma and neuroblastoma cells and stopped cell cycle progression in osteosarcoma cells in children [11]. Moreover, it was found that CB1 expression may help foreshadow the shrinking of lowgrade gliomas in children [11]. Another review on the role of cannabinoids in pediatric oncology indicated that a majority of previous studies were based on acute lymphoblastic leukemia, suggesting that cannabinoids have the ability to eliminate cancer cells in vivo and in vitro [12].…”
Section: Use Of Cannabis In Cancer Treatmentmentioning
confidence: 99%
“…Schab and Skoczen found that cannabinoids hindered the growth of rhabdomyosarcoma and neuroblastoma cells and stopped cell cycle progression in osteosarcoma cells in children. Moreover, they reported that CB1 expression may help foreshadow the shrinking of low-grade gliomas in children [ 16 ]. Another review on the role of cannabinoids in pediatric oncology indicated that a majority of previous studies were based on acute lymphoblastic leukemia and suggested that cannabinoids have the ability to eliminate cancer cells both in vivo and in vitro [ 17 ].…”
Section: Palliative Cannabis-based Treatments For Cancermentioning
confidence: 99%
“…However, micronutrient deficiencies have been linked to changes of bacterial species in the human gut microbiota affecting the host regulation of immune responses. Moreover, malnutrition is one of the common symptoms of cancer [ 81 ]. The supply of selected elements and vitamins could promote the richness of the intestinal microbiome and increase the amount of bacteria that are vital to higher effectiveness of oncological treatment ( Table 2 ).…”
Section: Micronutrients Gut Microbiome and Cancermentioning
confidence: 99%